Customer Satisfaction Factors: Examining the Impact of Digital Marketing and Destination Image on Crown Holidays - Prasetyo, Stephanie; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
Travel is currently a trend that is favored by young people. Gen Z who wants healing without the hassle of searching about the intended location only needs to make a reservation at an agency that provides tour & travel services, this service is also usually cheaper than traveling alone to the intended destination. Crown Holidays is one of the companies that provide these services both domestically and abroad. This study aims to see the influence between digital marketing and destination image in increasing customer satisfaction at Crown Holidays. The sample was obtained using the Hair et al formula so that 130 respondents were obtained. The results of the study partially show that digital marketing and destination image have a positive and significant effect on customer satisfaction at Crown Holidays. Simultaneously, both digital marketing and destination image variables affect customer satisfaction at Crown Holidays. The coefficient of determination test results shows a relationship between digital marketing and destination image with customer satisfaction at Crown Holidays. Crown Holidays is expected to use digital marketing as an effective marketing tool and evaluate the destination image of the destination before setting a tour & travel schedule.